2010
DOI: 10.1371/journal.pone.0015477
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Events Lead to Dendritic Spine Loss in Triple Transgenic Alzheimer's Disease Mice

Abstract: The pathology of Alzheimer's disease (AD) is characterized by the accumulation of amyloid-β (Aβ) peptide, hyperphosphorylated tau protein, neuronal death, and synaptic loss. By means of long-term two-photon in vivo imaging and confocal imaging, we characterized the spatio-temporal pattern of dendritic spine loss for the first time in 3xTg-AD mice. These mice exhibit an early loss of layer III neurons at 4 months of age, at a time when only soluble Aβ is abundant. Later on, dendritic spines are lost around amyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
135
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(144 citation statements)
references
References 53 publications
8
135
1
Order By: Relevance
“…Although plaques and tangles have traditionally been regarded as the main histopathological hallmarks of AD, a large body of evidence accumulated over the past decade suggests that soluble forms of these proteins are sufficient to trigger the development of the neurotoxicity process in AD (Berger et al., 2007; Bittner et al., 2010; Chabrier, Cheng, Castello, Green & LaFerla, 2014; Forner et al., 2017; Guerrero‐Munoz, Gerson & Castillo‐Carranza, 2015; Muller‐Schiffmann et al., 2016; Shankar et al., 2008; Spires‐Jones & Hyman, 2014; Tu, Okamoto, Lipton & Xu, 2014). These studies have clearly shown that soluble Aβ and tau oligomers are toxic to synapses and that the accumulation of these soluble isoforms correlates significantly with synaptic and memory impairments (Berger et al., 2007; Bittner et al., 2010; Chabrier et al., 2014; Forner et al., 2017; Guerrero‐Munoz et al., 2015; Muller‐Schiffmann et al., 2016; Shankar et al., 2008; Spires‐Jones & Hyman, 2014; Tu et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although plaques and tangles have traditionally been regarded as the main histopathological hallmarks of AD, a large body of evidence accumulated over the past decade suggests that soluble forms of these proteins are sufficient to trigger the development of the neurotoxicity process in AD (Berger et al., 2007; Bittner et al., 2010; Chabrier, Cheng, Castello, Green & LaFerla, 2014; Forner et al., 2017; Guerrero‐Munoz, Gerson & Castillo‐Carranza, 2015; Muller‐Schiffmann et al., 2016; Shankar et al., 2008; Spires‐Jones & Hyman, 2014; Tu, Okamoto, Lipton & Xu, 2014). These studies have clearly shown that soluble Aβ and tau oligomers are toxic to synapses and that the accumulation of these soluble isoforms correlates significantly with synaptic and memory impairments (Berger et al., 2007; Bittner et al., 2010; Chabrier et al., 2014; Forner et al., 2017; Guerrero‐Munoz et al., 2015; Muller‐Schiffmann et al., 2016; Shankar et al., 2008; Spires‐Jones & Hyman, 2014; Tu et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have clearly shown that soluble Aβ and tau oligomers are toxic to synapses and that the accumulation of these soluble isoforms correlates significantly with synaptic and memory impairments (Berger et al., 2007; Bittner et al., 2010; Chabrier et al., 2014; Forner et al., 2017; Guerrero‐Munoz et al., 2015; Muller‐Schiffmann et al., 2016; Shankar et al., 2008; Spires‐Jones & Hyman, 2014; Tu et al., 2014). In addition, we have also demonstrated that Aβ oligomers modulate the development of tau pathology and accelerate cognitive and synaptic impairments (Chabrier et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has demonstrated that A␤ causes tau to wander into dendrites, leading to loss of synapses, spines, and microtubules (7)(8)(9). In 3xTg-AD mice harboring a knockin mutation for presenilin 1 (PS1, M146V) and transgenes for amyloid precursor protein (APPswe) and tau (tauP301L), spine loss occurs exclusively at dystrophic dendrites that accumulate both A␤ oligomers and hyperphosphorylated tau intracellularly (10), and it is the phosphorylation of tau that causes the protein to stray (11). Previous publications have shown that A␤ induces phosphorylation of tau at serine and threonine residues via a myriad of signaling cascades.…”
mentioning
confidence: 99%
“…A previous study, aimed at analyzing the kinetics of dendritic spine loss within the somatosensory cortex in 3xTg-AD mice, by means of long-term two-photon in vivo imaging, has shown that dendritic spine loss did not occur in this region before 13 months of age. 27 Thus, the deficiency of spines that we observe in grafted neurons occurs earlier and is more severe than in the 3xTg-AD host. This suggests that the development of new spines in grafted cells is more severely affected than the already formed and stabilized spines of the host.…”
Section: Discussionmentioning
confidence: 66%